1: Checking the oil level on your diesel powered maize shelling machine. - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2021)
A step-by-step guidance on how a farmer can check if the lubricant (oil) levels within the machine is adequate. Having adequate lubricant/oil levels ensures that the machine engine operates well and doesn't break-down. This video was developed with funding from USAID through the Africa RISING Ghana project which is led by the International Institute of Tropical Agriculture (IITA). The purpose of the video is not to instantly turn farmers into specialist technicians, but to empower them to be able to perform basic maintenance activities when they don't have access to technicians.